Rural prosperity initiative: propensity-score analysis of income and crop production effects from a comprehensive micro-irrigation program in Zambia - Nicoletti, Christopher Kevin, author; Kroll, Stephan, advisor; Graff, Gregory, committee member; Weiler, Stephan, committee member (Colorado State University. Libraries, 2011)
This study seeks to expand the current literature of the impacts of technology adoption for smallholder farmers. It does so through an empirical investigation of the relationship between micro-irrigation technology investment, farmer-group enrollment and five key income and crop-production indicators of smallholder farmer-households in four rural Zambian regions. Micro-irrigation technologies were purchased by farmer-households, and were not randomly assigned. As such, the paper utilizes a propensity-score matching methodology to reduce self-selection bias, thereby estimating the causal effects of micro-irrigation technology investment on household incomes and crop production. By stratifying the sample, impacts were estimated for six combinations of treatment using three distinct matching algorithms. Regional and gender-specific treatment effects were estimated for the impact of farmer-group enrollment with micro-irrigation investment, and for the incremental impact of micro-irrigation investment when the farmer-household is already enrolled in a farmer-group. The study finds robust and positive effects of micro-irrigation investment and farmer-group enrollment on total crop incomes and total crop revenues, for the whole sample. Regional impacts of technology investment are less robust because of sample size limitations, but remain positive and significant in two of the four intervention areas. Female- and male-headed households both had positive and robust impacts on crop incomes, but female-headed household treatment effects were larger in magnitude. The findings of this study suggest that investment in micro-irrigation technologies and enrollment in a farmer-group lead to higher crop incomes for smallholder farmers in Zambia, and may reduce gender gaps in farmer earnings.
Keywords: micro-irrigation; Zambia; propensity-score matching; monitoring and evaluation